MODEL KEBIJAKAN PENDIDIKAN DASAR ISLAM DI INDONESIA ERA PANDEMI COVID-19 - Muh Syauqi Malik; Erni Munastiwi (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
The COVID-19 pandemic was very unexpected, came very suddenly. Various sectors were affected, not only in Indonesia but also overseas. The most highlighted sector in this research is the education sector, and the education sector needs attention because education determines civilization's progress. Besides, primary education is the basis for higher education. This research focuses on the model of Islamic basic education policy in the era of the COVID-19 pandemic. Researchers used a qualitative approach to literature studies and case studies to test the policy model in more detail. The research subjects in this study included the Ministry of Education and Culture, the Ministry of Religion, the National Education Standards Agency, and the Head of MI Salafiyah Tajungsari, Tlogowungu District, Pati Regency. Data collection techniques using observation, interviews, and documentation. Data analysis used data reduction, data presentation, concluding, and verification. The method of testing the researchers' data validity was obtained by triangulating methods and triangulation of sources. The results show that the policy model issued by the Ministry of Education and Culture, Ministry of Religion, Government, and Madrasah is uncertain, meaning that it always develops following the development of COVID-19 in the area. Learning is carried out online using various supporting tools such as WhatsApp Group, Google Classroom, Google Forms, Video Conference, and others tailored to the conditions and situation of the local community. The policy model taken has gone through deliberation by experts so that the teaching and learning process continues even though it has to go through various obstacles and obstacles.